Treating PTSD in military personnel a clinical handbook - Moore, Bret A.; Penk, Walter; Friedman, Matthew J. (The Guilford Press, 2019)
Now revised and expanded, this state-of-the-science guide is edited and written by leading authorities. The volume covers the full range of effective treatments for posttraumatic stress disorder (PTSD) and helps clinicians gain competency for working with service members and veterans.